Wedding Contact Sheet #1 - Pickford, Joel:::::::::
This contact sheet suggests that most, if not all, of the photographs on this roll of film were shot by pioneering filmmaker Robert Drew. His wife appears in several frames and his trademark low camera angle is consistent throughout the roll.